The impact of market-oriented cooperation on food production performance in small-scale farms in rural China - Zhang, Cheng; Zhu, Yueji (Frontiers in Sustainable Food Systems, 2023)
Smallholder farmers in developing countries can significantly contribute to sustainable food production through market-oriented cooperation (MOC). MOC allows farmers to access machinery services and specialized labor, but it also carries economic costs that may impact food production performance in small-scale farms. This study attempts to uncover the association between farmers’ MOC participation and food production performance in small-scale farms in rural China, using a sample of 650 rice farmers in Jiangsu province. We employ a treatment effect model to detect the effect of farmers’ MOC participation on technical efficiency, and use the multivalued treatment effects model to explore the relationship between farmers’ intensity of MOC and technical efficiency. The results indicate that farmers’ MOC participation significantly increases technical efficiency of small-scale farms, with an inverted U-shaped correlation between MOC participation intensity and technical efficiency. A heterogeneity analysis based on production phases reveals that farmers tend to adopt MOC in machinery-driven phases with higher priority than in labor-driven phases. MOC in labor-driven phases, such as seedling and spraying, presents negative effect on technical efficiency. These findings highlight the crucial role of MOC in food production performance in small-scale farms, and provide insights for designing MOC strategies in different production phases in order to facilitate sustainable food production in developing regions. This research addresses the need for solutions to improve food production and consumption sustainability under agricultural transformation in developing countries. It also touches on the challenges and opportunities that producers face in adopting new practices and participating in the modern food supply chain.